Optimal hyperthermic intraperitoneal chemotherapy regimen for advanced and peritoneal metastatic gastric cancer: a systematic review and Bayesian network meta-analysis - Wang, Tianqi; Ma, Shengjie; Zhang, Shiwei; Aizezi, Yilihaer; Wang, Quan (Frontiers in Oncology, 2024)
BackgroundPeritoneal metastasis is one of the most common modes of spread of gastric cancer. Currently, surgical treatment combined with hyperthermic intraperitoneal chemotherapy (HIPEC) and systemic chemotherapy has demonstrated promising outcomes in both the treatment and prevention of peritoneal metastasis in gastric cancer. However, various HIPEC drug regimens are in clinical use, and their efficacy remains unclear. This study aims to evaluate the effectiveness of different HIPEC drug regimens in patients with advanced gastric cancer to determine the optimal therapeutic approach.MethodsThis study conducted a systematic review and Bayesian network meta-analysis. Patients in the experimental group underwent surgery combined with HIPEC and chemotherapy. The search period covered literature from database inception to June 1, 2024. Hazard ratios (HRs) with 95% confidence intervals (CIs) were used to evaluate overall survival (OS) as the primary outcome. Odds ratios (ORs) with 95% CIs were used to assess overall disease recurrence, peritoneal recurrence, and postoperative morbidity as secondary outcomes. To ensure scientific rigor and transparency, this study has been registered with PROSPERO (CRD42024533948).ResultsA total of 11 randomized controlled trials (RCTs) involving 1092 patients were included. Compared to surgery combined with chemotherapy, the regimens of cisplatin (HRs = 0.52, 95% CI: 0.38-0.73), mitomycin C (HRs = 0.99, 95% CI: 0.55-1.79), cisplatin plus fluorouracil (HRs = 0.60, 95% CI: 0.38-0.95), and oxaliplatin plus 5-fluorouracil (HRs = 0.53, 95% CI: 0.36-0.78) all demonstrated benefits in OS. The cisplatin (ORs = 0.16, 95% CI: 0.03-0.60) and mitomycin C (ORs = 0.03, 95% CI: 0-0.71) regimens also showed advantages in reducing peritoneal recurrence, with no impact on postoperative morbidity. Importantly, the cisplatin regimen was superior to other regimens in terms of OS and overall disease recurrence, achieving a balance between efficacy and safety.ConclusionsCompared to chemotherapy alone, HIPEC treatment shows significant benefits in OS without a notable disadvantage in postoperative morbidity. Although no single HIPEC regimen demonstrated clear benefits across all outcomes, the cisplatin regimen performed well in multiple aspects, indicating its potential for further research and clinical application.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=533948, identifier CRD42024533948.